Successful outcome of an ovarian ectopic pregnancy - Athavale, Umesh; Satia, Meena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Ovarian pregnancy is rare and a conspicuous variant of ectopic pregnancy and an accurate preoperative diagnosis is very challenging various advances in diagnostic modalities like Transvaginal ultrasonography has evolved in identifying an ovarian pregnancy. We report here one such case of 30 years old with severe lower abdominal pain and bleeding per vaginum following six weeks of amenorrhea confirmed as ovarian ectopic pregnancy consistent with Speigelberg’s criteria on ultrasonography. This case highlights the significance of 3D ultrasonography in the diagnosis. Histopathological report concluded it to be an ovarian ectopic pregnancy.